2005
DOI: 10.5751/es-01293-100131
|View full text |Cite
|
Sign up to set email alerts
|

Predator-Resembling Aversive Conditioning for Managing Habituated Wildlife

Abstract: Wildlife habituation near urban centers can disrupt natural ecological processes, destroy habitat, and threaten public safety. Consequently, management of habituated animals is typically invasive and often includes translocation of these animals to remote areas and sometimes even their destruction. Techniques to prevent or reverse habituation and other forms of in situ management are necessary to balance ecological and social requirements, but they have received very little experimental attention to date. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 53 publications
0
85
0
Order By: Relevance
“…The most adaptive response of prey to human activities and infrastructure may depend on whether top-down or bottom-up forces determine population size, and on the relative impact that humans have on different trophic levels. For example, selection for human-disturbed sites of a top-down controlled prey species might result in fitness gains if anthropogenic disturbances have stronger consequences on its predators than on its food supply [10]. Given that human infringement on wildlife habitat is increasing rapidly and extensively, some habitat selection tactics may become more adaptive following anthropogenic disturbance, while previously rewarding decisions may become maladaptive [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The most adaptive response of prey to human activities and infrastructure may depend on whether top-down or bottom-up forces determine population size, and on the relative impact that humans have on different trophic levels. For example, selection for human-disturbed sites of a top-down controlled prey species might result in fitness gains if anthropogenic disturbances have stronger consequences on its predators than on its food supply [10]. Given that human infringement on wildlife habitat is increasing rapidly and extensively, some habitat selection tactics may become more adaptive following anthropogenic disturbance, while previously rewarding decisions may become maladaptive [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Banff and Waterton NP, in Canada, has used trained dogs, with a professional dog-handler, to conduct predatorresembling aversive conditioning of habituated deer and elk [38]. For comparison purposes, Banff also conducts a very limited annual cull of the elk, which requires two trained staff instead of one dog handler, but accomplishes the desired task in a matter of hours, compared to the few weeks of the calving season over which aversive conditioning is conducted.…”
Section: Impacts On Population and Ecosystemmentioning
confidence: 99%
“…Aggressive charges often take place during the mating season when males are particularly aggressive and territorial, but just as often during calving seasons when mothers fiercely defend their young [37]. In Banff NP, most aggressive incidents by elk are done by females defending their calves during the spring calving season [38]. Even small herbivores can become dangerous too, such as the increasing problem of white-tailed deer attacks at the Southern University, USA, during deer fawning season [39].…”
Section: Impacts On Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the opposite effect has also been shown, wherein animals will eventually acclimatize to disturbance that is predictable (i.e., habituation), remaining in areas o f high activity, and in some instances, even attracted to these areas as they can provide protection from predators that may be more wary (Isbell and Young 1993, Kloppers et al 2005, Stankowich 2008 Where mountain goats have been observed to avoid areas o f disturbance, the avoidance has often been associated with a focal source disturbance, such as a drilling pad (Foster and Rahs 1983) or specific logging block on the landscape (Gordon and Wilson 2004). Focal-point disturbances may be more easily recognized on the landscape, and therefore avoided, than a more dynamic, unpredictable and dispersed form o f disturbance, such as heliskiing.…”
Section: Influence O F Helicopter Activity On Use O F Seasonal Rangesmentioning
confidence: 99%